(untitled) (Research, Society and Development, 2020)
Inserting polymers into the asphalt binder can improve rheological properties, making it possible to increase pavement performance and service life. Elastomeric polymers, found in tire rubber and plastomers such as PET, provide beneficial modifications added to the binder. This research aims to perform a comparative analysis of the rheological properties of adding micronized PET and crushed tire rubber to the asphalt binder CAP 50/70, by performing empirical and fundamental rheology tests in order to determine the degree of modification each polymer causes and which one promotes the best performance of the asphalt compound. The content that provided the most favourable results with the use of PET was the content of 8%, while with tire rubber it was observed that the insertion of 5% benefits more the properties of asphalt cement. The results found point to effectiveness in adding the residues to the asphalt binder, although PET showed more interesting gains in the characteristics of the asphalt mass in higher contents, while tyre rubber, even in the lower contents, would tend to decrease the parameters of workability of the coating.